Energy saving in wastewater treatment plants: A methodology based on common key performance indicators for the evaluation of plant energy performance, classification and benchmarking. (15th September 2020) - Sabia, G.; Petta, L.; Avolio, F.; Caporossi, E.
Graphical abstract: Highlights: A methodology for wastewater plants energy efficiency estimation is presented. Process data easy-to-define are used to calculate Key Performance Indicators. A global energetic index allows plant classification, labelling and benchmarking. A rough estimate of the potential margins for energy savings is provided. A case study shows the steps to carry out the proposed methodology. Abstract: Wastewater treatment plants are a major energy user in the urban water cycle with an energy demand estimated in several countries in about the 1% of the overall national energy use. Nevertheless, the sector offers wide opportunities for energy saving and recovery to be fostered in order to reduce economic and environmental impacts. Nowadays, a consolidated procedure to assess energy performances in the wastewater sector is still not available. This work proposes a methodology for the evaluation, benchmarking and labelling of energy performances of wastewater treatment plants, based on easy-to-define data related to energy use and operative parameters. Statistical techniques are applied to validate input data and the step-by-step derived outcomes. Common key performance indicators were calculated and linearly aggregated in a global index able to convey the wastewater treatment plant energy performance. Such index allowed to carry out comparisons among energy consumptions supported by a dedicated built-up database collecting sectorial data, considered as a reference. A case study based on 10 selected wastewater treatment plants is proposed. The methodology led to derive a clear and affordable overview of the analysed plant energy performances. Moreover, the benchmarking analysis allowed to get, on the basis of the differences between the calculated global index values, a rough estimation of the potential energy gains achievable if suitable measures for ameliorating the plant energy efficiency performance are adopted. For three of the selected plants, the margins for energy savings resulted higher than 60%. The methodology suggests to focus on such cases by carrying out specific on-site inspection to detect energy use inefficiencies and define suitable actions addressed to save energy and enhance the system sustainability. In this view, the proposed procedure could also be applied with the aim of prioritizing actions to pursue energy savings among a large set of wastewater treatment plants.